2021
DOI: 10.3390/cancers13092100
|View full text |Cite
|
Sign up to set email alerts
|

BLBP Is Both a Marker for Poor Prognosis and a Potential Therapeutic Target in Paediatric Ependymoma

Abstract: Paediatric ependymomas are aggressive, treatment-resistant tumours with a tendency towards relapse, consistent with a sub-population of therapy-resistant cancer stem cells. These cells are believed to derive from brain lipid binding protein (BLBP)-expressing radial glia, hence we proposed that BLBP may be a marker for ependymoma therapy resistance. BLBP protein expression correlated with reduced overall survival (OS) in patients from two trials (CNS9204, a chemotherapy-led infant trial—5 y OS 45% vs. 80%, p = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Ependymomas are the second most common type of malignant pediatric brain tumor. Forty percent of cases remain incurable, and the 5-year survival in infants with is only 40%-52% (Gajjar et al, 2014;Sabnis et al, 2021). Medulloblastoma is the highest degree of intracranial malignancy of the glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Ependymomas are the second most common type of malignant pediatric brain tumor. Forty percent of cases remain incurable, and the 5-year survival in infants with is only 40%-52% (Gajjar et al, 2014;Sabnis et al, 2021). Medulloblastoma is the highest degree of intracranial malignancy of the glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Sabnis et al. identified a subpopulation of BLBP -expressing CSCs in pediatric EPN patients, that correlated with increased susceptibility to relapse or death ( 24 ). In this study, they investigated the ability to target and inhibit BLBP by PPAR (peroxisome proliferator-activated receptors) antagonists, utilizing the BLBP high expressed ST-EPN neurosphere cell line DKFZ-EP1NS ( 24 ).…”
Section: Supratentorial Ependymomasmentioning
confidence: 99%
“…identified a subpopulation of BLBP -expressing CSCs in pediatric EPN patients, that correlated with increased susceptibility to relapse or death ( 24 ). In this study, they investigated the ability to target and inhibit BLBP by PPAR (peroxisome proliferator-activated receptors) antagonists, utilizing the BLBP high expressed ST-EPN neurosphere cell line DKFZ-EP1NS ( 24 ). Investigators treated the ST-EPN spheres with PPAR antagonists and observed both a significant reduction of BLBP expression as well as reduced cell viability and migration, highlighting CSCs and its subsets as potential therapeutic targets to reduce tumor invasion and progression ( 24 ).…”
Section: Supratentorial Ependymomasmentioning
confidence: 99%
“…A combination of GSK126 and atorvastatin, a cholesterol biosynthesis inhibitor, showed good results in a murine DIPG model [173], and LXR-623, an agonist of LXR, has been found to be very effective in killing GBM cells in a xenograft model by depleting cholesterol levels [188]. Fatty acid uptake by pediatric ependymoma cells in a 3D spheroid has been also targeted using GW9662 through inhibiting the brainlipid-binding protein (BLBP or FABP7) gene expression [176]. In addition to molecules targeting lipid-related pathways, other drugs of a lipid nature are being investigated.…”
Section: Current Trends In the Treatment Of Pediatric Neurological Tu...mentioning
confidence: 99%